Fertility Enhancing Activities of Bioactive Components of Cochlospermum planchonii Rhizome on Cisplatin Induced Reproductive Dysfunctions in Sprague-Dawley Rats - Sunday Aderemi Adelakun; Busuyi Kolade Akinola; Grace Temitope Akingbade (Tehran University of Medical Sciences, 2019)
Objective: Cisplatin has been established to cause reproductive dysfunction; Cochlospermum planchonii is globally used in folklore medicine and has numerous therapeutic benefits. This study focused on fertility enhancing activities of Cochlospermum planchonii (Cp) on cisplatin-induced reproductive dysfunctions. Materials and methods: Total of 30 male and 30 female adult Sprague-Dawley rats were used for this study. The male rats randomly assigned into Group A (control) was given normal saline 2 ml/kg, Group B, C, D and E rats received(single dose of 8 mg/kg Cisplatin (i.p.) on the first day), (500 mg/kg body weight (bwt) of Cponce once daily for 14 days), (single dose of 8 mg/kg Cisplatin (i.p.) on 1st day followed by 500 mg/kg bwt of Cp once daily for 14 days) and (single dose of 8 mg/kg Cisplatin on first day followed by 50 mg/kg vitamin C for 14 days). Parameters tested include reproductive hormones, testicular histology, testicular antioxidants, semen parameters and fertility test. Results: Histological profile of the testes revealed derangement of the testis cytoarchitecture; Seminiferous epithelium, body, testes, accessory sex organs weight and sperm parameters, were significantly reduced (p <0.05). Hormonal assay showed significant changes in testosterone (p< 0.05) while luteinizing hormone and follicle stimulating hormone remained unchanged following cisplatin administration and a marked improvement was observed after Cochlospermum planchonii administration. Similarly, Cochlospermum planchonii improved the reduction of antioxidant parameters (SOD, CAT, GPx and GSH) and the increased MDA caused by cisplatin ingestion. Conclusion: Cochlospermum planchonii may thus offer protection against free radical mediated oxidative stress of rats with cisplatin induced reproductive dysfunction.